Study the Effect of Intraperitoneal Dexamethasone, Dexmedetomidine, and Their Combination on PONV After Laparoscopic Cholecystectomy: A Randomized Triple-Blind Trial - Hany Bauiomy; Neveen A. Kohaf; Mohammed Saad; Zaky Ftouh Rashed; Ahmed M. Abosakaya (Anesthesiology Research and Practice)
Trial Registration: ClinicalTrials.gov identifier: NCT05988671